Factors associated with humoral hypercalcemia of malignancy stimulate adenylate cyclase in osteoblastic cells. - Rodan, S B (1983)
The culture media of three cell lines, a human prostate carcinoma (PC3), a rat Leydig cell tumor (Rice-500), and a rat carcinosarcoma (WRC-256), that were derived from tumors associated with humoral hypercalcemia of malignancy (HHM), were examined for stimulation of adenylate cyclase in ROS 17/2.8 osteoblastic cells and for bone resorptive activity in culture. Cells from a nonhypercalcemic variant of the WRC256 tumor served as control. Extracts from three solid human tumors, a lung adenocarcinoma from a patient with HHM and two adenocarcinoma from normocalcemic patients (lung and colon), were also examined for adenylate cyclase stimulation. We found excellent correlation between stimulation of cyclic AMP accumulation in ROS 17/2.8 cells and bone resorbing activity in culture, or production of HHM in vivo. Stimulation of adenylate cyclase by HHM factors was inhibited by the parathyroid hormone competitive inhibitor, [8norleucyl, 18norleucyl, 34tyrosinyl] bovine parathyroid hormone (3-34) amide.